The Role of Central Complex Neurons in Prey Detection and Tracking in the Freely Moving Praying Mantis (Tenodera sinensis) - Wosnitza, Anne; Martin, Joshua P.; Pollack, Alan J.; Svenson, Gavin J.; Ritzmann, Roy E. (Frontiers in Neural Circuits, 2022)
Complex tasks like hunting moving prey through an unpredictable environment require high levels of motor and sensory integration. The animal needs to etect and track suitable prey objects, measure their distance and orientation relative to its own position, and finally produce the correct motor output to approach and capture the prey. In the insect brain, the central complex (CX) is one target area where these integrations are likely to take place. In the study presented here, we performed extracellular multi-unit recordings within the CX of freely hunting praying mantises (Tenodera sinensis). Initially, we recorded neural activity from freely moving mantises as they hunted live prey. These recordings clearly showed activity in cells that either reflected the mantis’s own movements or the actions of a prey individual which the mantis focused upon. In the latter cases, activity increased as the prey moved and decreased when it stopped. Interestingly, cells ignored movement of other prey than the one to which the mantis attended. To obtain quantitative data, we generated simulated prey targets presented on an LCD screen positioned below the clear floor of the arena. The simulated target oscillated back and forth at various angles and distances. We identified populations of cells whose activity patterns were strongly linked to the appearance, movement, and relative position of the virtual prey. We refer to these as sensory responses. We also found cells whose activity preceded orientation movement toward the prey. These we call motor responses. Some cells showed both sensory and motor properties. Stimulation through the tetrodes in some of these preparations could also generate similar movements. These results suggest a crucial importance of the CX to prey-capture behavior in predatory insects like the praying mantis and hence further emphasize its role in behaviorally and ecologically relevant contexts.